2004
DOI: 10.1177/1082013204044828
|View full text |Cite
|
Sign up to set email alerts
|

Osmotic Dehydration and Freezing as Combined Processes on Apple Preservation

Abstract: Combined processes effects of osmotic dehydration in sucrose solutions and freezing on apple cubes preservation were analysed. Two multifactorial experimental designs, in two levels, were conducted consecutively to quantify the effects of the following factors: temperature, osmotic dehydration time, concentration of the osmotic medium and freezing rate. The response variables considered were: sensory evaluation, colour, texture, water activity ( aw) and reducing and total sugars. The first experimental design … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
16
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 18 publications
2
16
0
1
Order By: Relevance
“…Several works have been carried out on the osmotic dehydration of fruit and vegetables such as pepper (Chenlo, 2006), apple , carrot (Singh et al, 2006), potato (Eren & Kaymak-Ertekin, 2007) and strawberry (Taiwo et al, 2003). It has also been discovered that ultrasound influences the water diffusivity, drying time, water activity and rehydration ratio of fruit and vegetables (C arcel et al, 2007;Kowalski & Szadzi nska, 2014). Ultrasound frequency of 20 kHz and above has an alternative expansion and compression effect on the solid sample which enhances the removal of water from the sample (McClements, 1995;Fernandes et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Several works have been carried out on the osmotic dehydration of fruit and vegetables such as pepper (Chenlo, 2006), apple , carrot (Singh et al, 2006), potato (Eren & Kaymak-Ertekin, 2007) and strawberry (Taiwo et al, 2003). It has also been discovered that ultrasound influences the water diffusivity, drying time, water activity and rehydration ratio of fruit and vegetables (C arcel et al, 2007;Kowalski & Szadzi nska, 2014). Ultrasound frequency of 20 kHz and above has an alternative expansion and compression effect on the solid sample which enhances the removal of water from the sample (McClements, 1995;Fernandes et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Some authors (Marin, Cano, & Fuster, 1992;Moraga, Martinez-Navarrete, & Chiralt, 2006;Skrede, 1996) have investigated chemical modifications during freezing which are responsible for pH, soluble solid, water content or color changes of frozen/thawed fruits. However, only a few authors have studied physical and chemical changes related to frozen fruit quality after freezing and only for one fruit category at a time: apples (Bunger, Moyano, Vega, Guerrero, & Osorio, 2004), mangoes (Botosoa, Chapleau, & Le-Bail, 2004) and raspberries (González, de Ancos, & Cano, 2002). Moreover, since freezing conditions were generally different and rarely characterized, it was difficult to compare the freezing effects.…”
Section: Introductionmentioning
confidence: 99%
“…Dermesonlouoglou et al (2007) have shown that the quality of frozen tomato can significantly be improved by osmotic dehydration as a prefreezing treatment. Bunger et al (2004) have considered osmotic dehydration of apple cubes prior to freezing. Dehydrofrozen apple cubes obtained high scores from potential customers.…”
Section: Introductionmentioning
confidence: 99%